Microbial invertases: A review on kinetics, thermodynamics, physiochemical properties. Issue 8 (August 2015) - Nadeem, Habibullah; Rashid, Muhammad Hamid; Siddique, Muhammad Hussnain; Azeem, Farrukh; Muzammil, Saima; Javed, Muhammad Rizwan; Ali, Muhammad Amjad; Rasul, Ijaz; Riaz, Muhammad
Highlights Background/history of invertases. Production, purification, physiochemical, kinetic and thermodynamic characterization of microbial invertases. Beneficial effects of invertases on human health. Industrial applications and future prospects of invertases. Phylogenetic analysis of invertases.